2000
DOI: 10.1152/ajpregu.2000.278.1.r255
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent reductions in blood pressure and metabolic rate during fasting in the unrestrained SHR

Abstract: Fasting produces multiple cardiovascular, metabolic, and behavioral responses. To examine the interrelationship between these responses, male spontaneously hypertensive rats (SHR; n = 8) implanted with cardiovascular telemetry devices were housed in metabolic chambers at 23 degrees C for 22-h daily measurements of physiological variables. The experimental apparatus was designed so that ingestive behavior was detected by photobeams and locomotion was detected by a load sensor. Cardiovascular and metabolic statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 44 publications
5
48
0
Order By: Relevance
“…Studies on the effects of 48-72-h fasting on physical activity in rodents have given conflicting results, indicating increased (Overton et al, 2001), decreased (Williams et al, 2000) or no change in physical activity (Nagashima et al, 2003). During long-term chronic food restriction in rodents however, an increase in physical activity is generally observed.…”
Section: Effects Of Energy Deficit On Physical Activity In Rodentsmentioning
confidence: 99%
“…Studies on the effects of 48-72-h fasting on physical activity in rodents have given conflicting results, indicating increased (Overton et al, 2001), decreased (Williams et al, 2000) or no change in physical activity (Nagashima et al, 2003). During long-term chronic food restriction in rodents however, an increase in physical activity is generally observed.…”
Section: Effects Of Energy Deficit On Physical Activity In Rodentsmentioning
confidence: 99%
“…20 After surgery, animals were given subcutaneous injections of 30 mg kg -1 buprinex analgesic (Henry Schein Inc., Melville, NY, USA) and intramuscular injections of 60 mg kg -1 of cefazolin (Henry Schein Inc.) as a prophylactic.…”
Section: Surgerymentioning
confidence: 99%
“…The remaining 41 FBNF1 rats were maintained on standard chow and prepared for study shortly after reaching a stable body weight above 300-350 g. The apparatus and procedures used for determination of energy expenditure and locomotor activity have been described previously. 19,20 Briefly, rats were housed in individual polycarbonate 20 l cages each fitted for open circuit respirometry. Oxygen consumption and carbon dioxide production were continuously measured 23 h day -1 .…”
mentioning
confidence: 99%
“…It is also a very prominent feature of the metabolic syndrome (MetS). Insulin resistance and central obesity, recognized as the main factors involved in the pathophysiology of the MetS, contribute to elevated blood pressure, which further promotes vascular damage in cardiac, renal and brain tissue (Sowers et al, 2004;Wang and Hoy, 2004 Several epidemiological studies from different populations have reported significant association between different anthropometric indicators (such as waist circumference, body mass index (BMI) and waistheight ratio) and blood pressure levels (Williams et al, 2000;Duvnjak et al, 2008;Kjeldsen et al, 2008). These associations between body fatness using different indices have been consistently observed but remain poorly understood and the mechanistic explanations for the phenomenon are still being debated and no biological model of the process has been established (Rufus et al, 2008).…”
Section: Introductionmentioning
confidence: 99%